The Effect of Traditional Gold Mining toward the Socio-Economic and Environmental Aspect in Sepauk District Sintang Regency - Depy Anggraini; Soemarno Soemarno; Harsuko Riniwati (Graduate Program, 2019)
The gold mining in Sepauk District in the watershed and the mainland causes problems from the economic, social, and environmental standpoint. The purpose of this study is to analyze the social, economic, and environmental conditions in Sepauk District of Sintang Regency and the impact of the traditional gold mining on the social, economic, and environmental aspects. This study uses a descriptive qualitative model where researchers collect data through observations, interviews, and documentation. The social aspects of education have increased considerably; health is still very limited with the lack of health facilities and medical personnel; age and sex, no children and women employed, average working age for work; tribe and religion is not a problem to work as a miner. Economic aspect in the form of livelihood change, formerly majority farming and now become miner and income enough increase and its environmental aspect is caused by road damage, river water pollution, land damage and noise. The traditional gold mining activities have had a positive impact such as improving the welfare of the people and reducing unemployment; yet, it also brings negative impact, such as health problems, road damage, river pollution, land damage, noise pollution, and land conflicts. Thus, it is recommended that the government guide and supervise the community in conducting the mining activities.Keywords: Economy, Environment, Gold mining, Social